PROFESSOR V. M. GOLOVTSYN – FOUNDER OF SCHOOL FOR ELECTROPROSRECTING IN THE NATIONAL TARAS SHEVCHENKO UNIVERSITY KYIV (TO 100-YEARS BIRTH ANNIVERSARY) - HRYSHCHUK, P.; PRODAIVODA, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
Biographic information about professor, head of department of the geophysical methods of exploration and prospecting of mineral deposits in Kyiv University – V. M. Golovtsyn are described. In paper are described his scientific and organizational activity in Russia and on Ukraine.